Students’ reflection on co-design: A cross-disciplinary collaboration between two SADC countries - Mchunu, K.J.; Moodley, S. (South African Journal of Higher Education, 2019)
This reflective article responds to the question: “What values and lessons can be gained from co-design in a culturally and disciplinarily diverse cross-university student project?” The Polar Project is regarded as just such an initiative and was intended to boost innovative product development across fields of study between two higher education institutions (HEIs) located in Southern African Development Community (SADC) region countries. As lecturers, facilitators and mentors, the article’s authors adopted a qualitative and interpretive approach for analysing student “reflections-in-action”, using both reports and reflective questionnaires during the project’s co-design process. We formulated our own analysis methods for the process of critical reflection, based on Schön’s (1987) “reflection-on-action” model, to establish a way forward for the project. Through these reflections, the following critical themes were identified: (1) rewards for cross-cultural exchange; (2) multiple appreciations for collaboration; and (3) communication and miscommunication in cross-disciplinary groups. These themes provide an account of the practical implications for extracurricular activities geared towards the agenda of internationalising higher educational practices, such as those applied in conducting this project. The contribution we hope to make is that, as HEIs enter onto internationalisation agendas, the voices and experiences of students should be recognised if, as important beneficiaries of the university system, they are to be properly considered.